Analisis Backswing Dan Penggunaan Star Excursion Balance Test (SEBT) Terhadap Hasil Lemparan Shooting Petanque - Munir, Ahmad Sirodjul; Irawan, Fajar Awang (Journal of Sport Science and Education, 2021)
Petanque shooting do not always hit the target. Coordination between body segments and arm swings is an obstacle related to the accuracy of the shooting. The purpose of this study was to analyze the backswing and balance of the petanque shooting. The method in this study used quantitative descriptive and data collection used tests and measurements through the Star Excursion Balance Test (SEBT) and shooting precision tests. Technical analysis of data using Dartfish analysis software version 8.0. The results of this study indicated that the backswing analysis showed that the average of backswing angle was 109.5°, with a swing speed of 0.645m⁄s, and a release angle of 110.3°. The results of the shooting precision obtained by the sample have an average score of 19.6 and were included in the "medium" category. The conclusion of this study showed that the backswing analysis and the used of SEBT have a contributive relationship to the results of shooting petanque carried out. The number of shooting and the intensity that can be done can improved the athlete's performance, especially in providing recommendations and evaluations on shooting accuracy. Further research is expected to add research variables such as data on muscle strength and arm power to complete this research data.